Forensic and Legal Medicine Clinical and Pathological Aspects - Payne-James, Jason; Byard, Roger (Taylor & Francis, 2021)
A comprehensive and accessible resource covering all aspects of forensic and legal medicine.The text provides a foundation for those working in both the clinical and forensic aspects of care, and will also be an asset to those involved in the police or judicial systems. Including clear guidelines for practical applications, and further enhanced by its many illustrations and case examples,this text is a valuable resource in an increasingly complex field.The authoritative work is written for a wide audience including forensic pathologists, general pathologists, pediatric pathologists, forensic physicians, forensic scientists, coroners, emergency department physicians,judges, and legal practitioners.